Poling forces during roller skiing: effects of technique and speed - Millet, G. Y.; Hoffmann, M. D.; Candau. R. B.; Clifford, P. S. (Medicine & Science in Sports & Exercise, 1998)
PURPOSE: Although it has been reported that the majority of propulsive forces are generated through the poles with ski skating, no study has systematically examined poling forces among different skating techniques. The objective of the present study was to examine poling forces and timing during roller skiing on a 2.1% uphill. METHODS: Nine highly skilled cross-country skiers roller skied at three paced speeds and maximal speed using the V1 skate (V1), V2-alternate (V2A), V2 skate (V2), and double pole (DP) techniques while poling forces and timing were measured with piezoelectric transducers. RESULTS: Peak force (PF) values with the skating techniques were significantly lower than with DP and ranged from 18.9 +/- 3.1% of body weight (BW) to 31.5 +/- 5.6% BW across the speeds of the study. Average force over the entire cycle (ACF) increased with speed with DP, V2A and V1 (P < 0.01) but not with V2. PF and ACF were higher (P < 0.01) with V2 than V1 and V2A. Poling time was longer (P < 0.01) with V2A compared with V1 and V2. CONCLUSIONS: The results of this study suggest that 1) the use of the upper body is greater with V2 than with other skating techniques while there is a relatively greater reliance on the lower body for generation of the additional propulsive forces required to increase velocity, and (2) poling forces do not appear to be as effectively applied with V2 as with V2A.